Keteladanan Luqman Al-Hakim dalam Membentuk Akhlak Anak (Kajian Tafsir Surat Luqman Ayat 12-19) - Shofwatal Qolbiyyah (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2020)
This study aims to examine the exemplary of Luqman al-Hakim in Forming Child Morals in the letter Luqman verses 12-19. This type of research is library research with the maudlu'iy approach, which collects verses according to their central theme, then discusses and analyzes them so that they become a unified whole. The documentary data collection method was then analyzed using deductive and comparative analysis. The results showed that the will of Luqm al-Hakim in LuqmÃ¢n verses 12-19 included: Aqeedah Education, Birrul Walidain, Commands to establish Salat, Amar Ma'ruf Nahi Mungkar, and Budi Pekerti or Moral Education.